Fluorescence diffuse optical imaging for small animal study. - Lim, Shu Qiang. (2012)
The design of an all-optical anatomical co-registration for molecular imaging of small animals involves the consideration of several issues in regards of designing the experiment, optimization of data collected, economic and feasibility studies. Extensive literature review served as a crucial step to gain meaningful information on up-to-date imaging techniques and process models. Not many works in the literature have used theories to study dynamic fluorescence molecular imaging (DFMI) technique. Only a handful of papers can be found but even these authors confined to only studying the feasibility of which. In this report, the author aims to devise a way to improve the interpretation of in vivo optical images of targeted contrast agent by a co-registered anatomical overlay of the major internal organs of the small animal. The proposed idea is to capture images of fluorescence of the major internal organs and overlap it with general view of the mice so as to obtain exactly co-registered anatomical overlay images. After which, principal component analysis (PCA) to outline each organ’s distinctive time course, will be performed